The effectiveness of e‐health interventions for the treatment of overweight or obesity in children and adolescents: A systematic review and meta‐analysis. (7th November 2021) - Azevedo, Liane B.; Stephenson, John; Ells, Louisa; Adu‐Ntiamoah, Shirley; DeSmet, Ann; Giles, Emma L.; Haste, Anna; O'Malley, Claire; Jones, Daniel; Chai, Li Kheng; Burrows, Tracy; Collins, Clare E.; et al.
Summary: The aim of this systematic review and meta‐analysis was to examine the effectiveness of e‐health interventions for the treatment of children and adolescents with overweight or obesity. Databases were searched up to November 2020. Studies were randomized controlled trials where interventions were delivered via e‐health (e.g., computers, tablets, and smartphones, but not phone calls). Studies should target the treatment of overweight or obesity in children or their agent of changes and report body mass index (BMI) or BMI z ‐score. A meta‐analysis using a random‐effects model was conducted. Nineteen studies met the inclusion criteria, and 60% were of high quality. The narrative review revealed variation in behavior change strategies and modes of delivery. The pooled mean reduction in BMI or BMI z ‐score showed evidence for a nonzero effect (standardized mean difference = −0.31, 95% confidence interval −0.49 to −0.13), with moderately high heterogeneity between studies ( I 2 = 74%, p < 0.001). Subgroup analysis revealed high heterogeneity in studies with a high or unclear risk of bias. E‐health interventions can be effective in treating children and adolescents with overweight and obesity and should be considered by practitioners and policymakers. However, an understanding of the most effective and acceptable intervention components, long‐term benefits, and sustainability should be further studied.